Integrated multi-spectroscopic and molecular modeling techniques to study the formation mechanism of hidden zearalenone in maize. (30th July 2021) - Tan, Hongxia; Zhou, Hongyuan; Guo, Ting; Zhang, Yuhao; Ma, Liang
Graphical abstract: Highlights: Mechanism of the presence of hidden ZEN in maize is proposed. Binding of ZEN to zein can result in the "hidden" phenomenon of ZEN in maize. ZEN binds with zein through hydrophobic interaction and hydrogen bonds. ZEN-zein interaction affects ZEN migration and transformation during food processing. Abstract: Hidden mycotoxins have been reported to be "protected" by macromolecular substances to escape routine determination, but release to free mycotoxins under gastrointestinal conditions. Nowadays, the hidden zearalenone (ZEN) that binding with macromolecular zein has been found in maize. However, the binding mechanism of ZEN with zein in maize has not been clarified. In this study, the formation of ZEN-zein complex was investigated applying ultrafiltration, multi-spectroscopic and molecular modeling techniques. The steady-state and transient fluorescence analysis suggested the ZEN could interact with zein to form the complex driven by hydrophobic force and hydrogen bonds, which is in accordance with the molecular modeling studies. The conformational changes of zein induced by binding with ZEN were revealed by Fourier transform infrared spectroscopy (FTIR) and circular dichroism (CD). Elucidating the binding mechanism between zein and ZEN could help the development of detecting hidden ZEN and guarantee the safety of maize products.